Study on the vibration characteristics and influence range of buried dam pipeline - Lihui Gao; Jing Xu; Shuai Xing (Scientific Reports)
Abstract To alleviate water resource shortages and tensions and meet the water diversion needs of different river basins, buried (cross-dam) pipelines have become an essential component of water diversion projects. They are installed in levee projects in key river basins such as the Yellow River, Jingjiang River, and Beijiang River. Due to the complex engineering structure and multiple sources of vibration excitation, if vibrations propagate along the pipeline axis towards the surrounding levee, they could have an adverse impact on the stability and safe operation of the levee. To accurately identify the vibration and transmission characteristics of the buried pipeline dikes, determine its primary vibration sources, and clarify the propagation laws of pipeline vibrations within the levee, this study, based on prototype observation data and utilizing signal fusion processing technology, investigates the inherent vibration characteristics of the buried pipeline dikes from the perspectives of excitation, transmission, and response. At the same time, by introducing the “finite element-infinite element” theory, a coupled finite element-infinite element model is established for the pipeline, levee, anchor piers, support piers, foundation, and infinite half-space. This model is then used to analyze the site response induced by flow-induced vibration in buried pipeline levee structures. The results show that the primary vibration frequencies of the buried pipeline dike structure are the unit rotation frequency of 74.4 Hz and the blade vibration frequency of 24.8 Hz. These vibration sources originate from the pump unit and propagate outward along the pipeline axis. Using the transmission range of the vibration source as the basis for determining the vibration impact range, it was established that the horizontal vibration impact of the buried pipeline extends 10 m on either side of the pipeline axis, while the vertical vibration impact extends 7.5 m below the dike crest.